2016
DOI: 10.2119/molmed.2015.00250
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin Protects Mice from Lethal Sepsis by Modulating Immunometabolism Upstream of PKM2

Abstract: Sepsis is characterized by dysregulated systemic inflammation with release of early (for example, interleukin (IL)-1β) and late (for example, HMGB1) proinflammatory mediators from macrophages. Plumbagin, a medicinal plant-derived naphthoquinone, has been reported to exhibit antiinflammatory activity, but the underling mechanisms remain unclear. Here, we have demonstrated that plumbagin inhibits the inflammatory response through interfering with the immunometabolism pathway in activated macrophages. Remarkably,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 48 publications
3
25
0
1
Order By: Relevance
“…Consistent with this, Yang et al showed that pharmacological inhibition of PKM2 renders mice more resistant to lethal sepsis. This enhanced resistance was associated with reductions in both glycolysis and IL-1β production (22,76). These data, combined with our observations here, suggest that targeting aerobic glycolysis might represent a viable therapeutic strategy for treatment of inflammatory diseases.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with this, Yang et al showed that pharmacological inhibition of PKM2 renders mice more resistant to lethal sepsis. This enhanced resistance was associated with reductions in both glycolysis and IL-1β production (22,76). These data, combined with our observations here, suggest that targeting aerobic glycolysis might represent a viable therapeutic strategy for treatment of inflammatory diseases.…”
Section: Discussionsupporting
confidence: 65%
“…Nox4 was constitutively active, the elevated Nox4 expression directly translated to increase ROS production [32]. Increasing evidences demonstrated that Nox4 played a detrimental role in process of inflammatory diseases, including sepsis [3,30,33]. Here, our results clearly showed that Nox4 was significantly increased in LPSinduced septic mice, which was accompanied by increased inflammatory mediators and inflammatory cytokines production.…”
Section: Discussionsupporting
confidence: 57%
“…The NADPH oxidases are a major source of intracellular ROS generation in macrophages [29]. Meanwhile, NADPH oxidase-dependent ROS played a detrimental role in lethal innate immune response in sepsis [4,30]. The role of oxidative stress in septic pathogenesis has been well appreciated [3,4]; however, the mechanisms by which oxidative stress contributed to pathogenesis were not well defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations